Role of BMI in Matrix Delamination during Intervertebral Disc Degeneration. (May 2014) - Friedmann, A.; Schwan, S.; Heilmann, A.; Goehre, F.; Meisel, H. J.
Introduction: Intervertebral disc (IVD) degeneration is a natural process during aging, contributed by mechanical, genetic, and biochemical parameters. Interactions between these parameters cause an instance of matrix degeneration in IVD tissue on the macroscopic and microscopic scale. The process of disc degeneration by means of matrix destruction should be promoted by an increased body mass index (BMI) representing increased mechanical loadings. The objective is to determine and correlate tissue changes of IVD degeneration in different states under consideration of patients' BMI value. Materials and Methods: As part of a clinical study, human IVD tissues from 60 patients removed during standard sequestrectomy as neurosurgical treatment after disc herniations are investigated regarding their microstructure using scanning electron microscopy. Specimens' microstructure is investigated with focus on the delamination of the tissue matrix, as well as cellular changes. With digital image analyzing software, degeneration characteristics are evaluated and correlated with clinical relevant parameters. Results: Matrix delamination is identified by digital image analysis as microstructural destruction in disc degeneration closely related to patients BMI on the one hand but on the other hand not related to patients' age or gender. Cellular variations are proved as decrease in cell density and increase in cell size while creeping reduction of the thickness of the extracellular matrix. Conclusion: Due to the future development of regenerative therapies for IVD degeneration it is essential to understand the mechanism of degenerative processes in disc tissue. This study demonstrates that structural variations in the microscale are characteristically for disc degeneration and may be the link or trigger for prolapse of degenerated disc tissue. Disclosure of Interest None declared